Combine Your “Will” and “Able”: Career Adaptability’s Influence on Performance - Gao, Xueyuan; Xin, Xun; Zhou, Wenxia; Jepsen, Denise M. (Frontiers in Psychology, 2019)
Adaptivity and adaptability are two key elements representing one’s “willingness” and “ability” respectively in career construction theory framework. On the basis of career construction theory and complemented by the visual of resources in conservation of resources theory, the current study examines the joint effect of adaptivity and adaptability on career self-management which will further lead to a good performance. Using a sample of Chinese employees (N = 232), the study first examines the mediating role that career self-management plays between career adaptability and performance and then tests the moderating role of proactive personality. Results show career adaptability positively predicts performance, with this relationship partially mediated by career self-management. The positive effect of career adaptability on career self-management is stronger among those who are more proactive than less proactive. Further, the indirect effect of career adaptability on performance is stronger among proactive employees than those with lower levels of proactive personality. These findings provide implications for career construction and conservation of resources theories as well as practical implications for recruitment and training.